Mining traffic patterns from public transportation GPS data - Lipan, F; Groza, A (2010 IEEE International Conference on Intelligent Computer Communication and Processing, 2010)
Bus schedules submitted by public transportation companies often lack accuracy. Generally this relates to traffic being inconsistent over most parts of the road network. We set on finding a model for predicting these speed variations over GPS monitored bus routes, by using association rules, and then apply it on the local bus network of Cluj-Napoca, Romania.